2021
DOI: 10.1093/cid/ciab951
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Coronavirus Disease 2019 Pandemic on Human Immunodeficiency Virus Services: Findings from 11 Sub-Saharan African Countries

Abstract: Background Concerns about the effects of COVID-19 pandemic on health services span the globe. We examined its effects on HIV services in sub-Saharan Africa. Methods Data collected quarterly [Q1: October-December 2019; Q2: January-March 2020; Q3: April-June 2020; Q4: July-September 2020] from 1,059 health facilities in 11 countries were analyzed and categorized by stringency of pandemic measures. We conducted a difference-in-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
18
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 13 publications
4
18
1
Order By: Relevance
“…A multi-site cohort study carried out in 1059 health facilities located in 11 sub-Saharan countries (Angola, Burundi, Cote d'Ivoire, Democratic Republic of Congo, Eswatini, Ethiopia, Kenya, Mozambique, South Sudan, and Zambia) suggested a transient negative effect on HIV testing and ART initiation followed by rapid recovery since more stringent measures were over. No impact was noted on viral load suppression [23]. Similar transient trend was documented in three African countries (Uganda, Kenya, Nigeria) registering a temporary decrease in HIV clinic visit adherence early in the pandemic, and an increase in viral suppression later in the pandemic [24].…”
Section: Human Immunodeficiency Virus (Hiv)supporting
confidence: 75%
“…A multi-site cohort study carried out in 1059 health facilities located in 11 sub-Saharan countries (Angola, Burundi, Cote d'Ivoire, Democratic Republic of Congo, Eswatini, Ethiopia, Kenya, Mozambique, South Sudan, and Zambia) suggested a transient negative effect on HIV testing and ART initiation followed by rapid recovery since more stringent measures were over. No impact was noted on viral load suppression [23]. Similar transient trend was documented in three African countries (Uganda, Kenya, Nigeria) registering a temporary decrease in HIV clinic visit adherence early in the pandemic, and an increase in viral suppression later in the pandemic [24].…”
Section: Human Immunodeficiency Virus (Hiv)supporting
confidence: 75%
“…From a single tertiary hospital in India, researchers found that HIV testing dropped 57% in 2020 compared to 2019 with a similar decline for new diagnoses [16]. An analysis of HIV services in sub-Saharan Africa also saw HIV testing declines among general population clients; however, the decline associated with the initial COVID-19 wave was modest (∼3%) compared to our findings with a faster rebound [17]. In contrast, COVID-19 lockdowns in South Africa were found to correlate with nearly a 50% decline in testing in April 2020 with gradual improvement over time [18].…”
Section: Discussioncontrasting
confidence: 57%
“…Qualitative data from other cities around India supported the success of MMD (vs. single month as was standard) as well as field/home delivery of ART [10], suggesting that the impacts on ART might have been less than preventive and testing services. Analyses from sub‐Saharan Africa found similar patterns, with a substantially smaller impact on ART use compared to HIV testing [17, 18]. Among MSM living with HIV across 20 countries, 20% reported they were unable to see their HIV provider because of pandemic mitigation strategies—notably lower than reported interruptions in HIV testing [20].…”
Section: Discussionmentioning
confidence: 99%
“… 37 A study of routine data from 65 public sector primary care clinics in Kwazulu–Natal province, South Africa, 6 found that the number of HIV tests declined by nearly 50% at the start of the lockdown, with gradual improvement over the next 3 months to pre-lockdown levels. A study of 11 sub-Saharan African countries 21 found a small decline in number of HIV tests early in COVID-19. The decrease in HIV diagnoses may be due to NPIs reducing the number of newly-infected cases by affecting people's sexual activity.…”
Section: Discussionmentioning
confidence: 99%